Colombian Children in War Films: Operación E and Alias María. Issue 5 (May 2019) - Rocha, Carolina
Abstract : Two contemporary co-produced films, Operación E (Miguel Courtois, 2012) and Alias María (José Luis Rugeles, 2015), touch on events that took place in Colombia in recent history and in which the FARC participated. In this article I analyse these two films, suggesting that despite their different sources of financing, they are both anti-war films that employ two categories of the threatened child: the sick child in Operación E and the deprived child in Alias María. These categories stress the abuses committed by guerrillas and the important function of the 'child-savers' who, by protecting threatened children, stand for the hope of Colombian society.